Relevance of German Political Foundations for Comparative Educational Research - Adick, Christel; Giesemann, Maria (Journal of Education and Research, 2015)
German political foundations, mainly Friedrich-Ebert-Stiftung (FES) and Konrad-Adenauer-Stiftung (KAS), have a long tradition of political activism in Germany as well as internationally.  Founded after the Second World War, their mission was and is the promotion of democracy and civic education.  Likewise, they pursue these educational goals abroad, where they have been active for over 50 years.  But despite many years of experience in the field of political education across borders, the foundations have hardly been noticed in educational research.  Therefore, an international audience shall be made aware of the unique characteristics of the German party related political foundations as actors in the world.  This article will address the international dimensions of these organizations: how they operate across borders and what they offer in their educational dimensions.  This will show their close entanglement with the official German foreign policy and with the political parties to which they are affiliated in Germany.